If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cos(3x) + cos(5x) = 0 Remove parenthesis around (3x) cos * 3x + cos(5x) = 0 Reorder the terms for easier multiplication: 3cos * x + cos(5x) = 0 Multiply cos * x 3cosx + cos(5x) = 0 Remove parenthesis around (5x) 3cosx + cos * 5x = 0 Reorder the terms for easier multiplication: 3cosx + 5cos * x = 0 Multiply cos * x 3cosx + 5cosx = 0 Combine like terms: 3cosx + 5cosx = 8cosx 8cosx = 0 Solving 8cosx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '8'. cosx = 0 Simplifying cosx = 0 The solution to this equation could not be determined.
| 60x^2y-70x^4zw= | | 34-79=x | | 343-79=x | | 4k+3k+90+174=360 | | 28=.5x^2 | | Y=-6.75+8.54 | | 8(4q-5)-7q=2q-10 | | 13y+15=11x-25 | | x-79=2 | | 4k+3k=96 | | (3n+8)+n=54 | | 6(2+-1)+5=12-t | | (3/5x)^-1 | | 6(x*3)=21 | | 4p=160 | | 9r+6r+3=6r+3-r | | 2n+3(15)= | | 9x^2+24x+0=0 | | 2(8s+9)-4s=3(4s+5)-20 | | 34-x=2 | | 17ln(1-3x)=42 | | ln(4x-2)=7 | | 6x+20=360 | | 10X-1=10X-1 | | -12x-25=11-6x | | Y^3-y-6=0 | | 17x-9(5x-3)=1.14(x+3)-6 | | =cos(5y) | | x+(2x-1)=20 | | 3*37= | | 111/37=n | | (6+7)-(3x+4)= |